Essays on resource use, technology, and climate change - Yin, Di (2016)
This thesis consists of three self-contained essays on the topic of “resource use, technology, and climate change”. The first essay is a theoretical study from a global approach examining the effects of emissions abatement policy and energy R&D investments. The second and third essays are two empirical studies from a regional approach investigating the energy consumption, energy intensity, carbon emissions, and emission intensity in the APEC-17 countries. The first essay aims to investigate the impacts of emissions abatement policies and energy R&D investments on economic gains, abatement costs, resource use, and climate change over the time span from 2005 to 2155 in the framework of a two-sector multiple-resource hybrid model. It analyzes three emissions abatement policies: an optimal policy, a delayed policy, and a 2 ̊C policy proposed by the Paris Agreement 2015, and presents the heterogeneity in the impacts of R&D investments on energy efficiency and on backstop technology. It shows that the optimal policy leads to the least abatement costs compared to the delayed policy and the 2 ̊C policy. The more restrictive the policy is, the more severe economic damage is caused in the short run but the more economic welfare is gained in the long run. The key impact of R&D investments on energy efficiency is that it reduces the abatement costs by improving energy efficiency while the main impact of the R&D investments on backstop energy is that it lowers the costs of the backstop technology and further accelerates the substitution between fossil fuels and the backstop energy. The backstop energy replaces the fossil fuels ten years earlier in the case with R&D investments in backstop technology than the BAU case. The second essay aims to find the drivers for the change of energy consumption and carbon emissions in 17 APEC countries over twenty years from 1990 to 2010 using the temporal Index Decomposition Analysis (IDA). Nine developed countries and eight developing countries show different patterns of energy consumption and carbon emissions over twenty years. It also examines the impact of extreme macroeconomic events on the drivers. An economic shock appears to affect the level of energy consumption and carbon emissions through an activity effect - a slow economic growth causing low levels of energy consumption and carbon emissions, but it appears not to change the structure of energy consumption and the level of energy efficiency in the short run. The third essay aims to analyze whether there is a convergent pattern of energy and carbon intensity in the sub-regions of the APEC and to examine the factors that affect the absolute difference in energy and carbon intensity across the APEC countries using a spatial IDA method. It seeks to answer two broadly defined questions: the trends of energy intensity and carbon intensity within and between nine developed countries and eight developing countries in the APEC region and the role of three economic cooperation organizations within the APEC region. It finds that over twenty years, nine developed countries do not show a clear trend in energy and carbon intensity, while eight developing countries show a convergent tendency in energy and carbon intensity over years mainly contributed by China. The analysis of economic cooperation shows that a strong connected regional cooperation (e.g., the ASEAN) regarding economic development and energy efficiency helps enhance the convergence of energy and carbon intensity.